Американское оратороведение как гуманитарная наука - Овчинникова, Альбина Петровна; Овчиннікова, Альбіна Петрівна; Ovchinnikova, Al'bina (Одеса : Юрид. л-ра, 2012)
In the article contained comparative analysis of understanding of humanities in Europe and America on the example of acquisition of scientific status American Criticism of Oratory.
Овчинникова А. П. Американское оратороведение как гуманитарная наука / А. П. Овчинникова / Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю .П. Аленін [та ін.] ;МОНмолодьспорт України, НУ «ОЮА». – Одеса : Юрид. л-ра, 2012. – Вип. 67. - С. 164-171.
Keywords: оратороведение; правоведение; системный подход; нормативно-гуманитарная наука; ораторознавство; правознавство; системний підхід; нормативно-гуманітарна наука; Criticism of Oratory; jurisprudence; systems approach; normative-humanitarian science